Definition of efficiency indicator and study of its main function as an optimization criterion - Lutsenko, Igor (Eastern-European Journal of Enterprise Technologies, 2016)
The problem of development rates maximizing of any business structure is solved by system processes optimization, and the best choice taking from a set of available alternatives. In order to solve these problems, an indicator that can be trusted to a central place in the technology of the optimum solutions is needed. Especially it is urgent where full automation of control processes is necessary. This responsibility involves the careful selection and verification of the indicators claiming to be the optimization criterion. According to the retrospective analysis, in this issue it is possible to allocate two interconnected problems. The first problem is an uncertainty of the “optimization” concept. In fact, the optimization process, for today, is associated with extremum search of some function. In this regard, the second problem is related to the fact that as an optimization criterion, forming the function, it is proposed to use a variety of indicators. In this work the essence of an efficiency indicator is revealed. The structure of this indicator and the properties which such indicator has to possess are defined. A number of classes of reference operations were created. Each such class provides a possibility of testing those qualities which the efficiency indicator applying for a role of optimization criterion has to possess. The indicator which has cybernetic structure and successfully passed test on all classes of reference operations has been developed. Results of use of the developed indicator as optimization criterion in the system of liquid portion heating have been given. Definition for category “efficiency” and “efficiency indicator” has been given. The received results can be useful to developers of cross-disciplinary indicators, specialists in control processes automation and business processes optimization.